Utrasonographic monitoring of uterine motility in infertile women with adenomyosis = Ультрасонографический мониторинг маточной перистальтики у бесплодных женщин с аденомиозом - I. Z. Gladchuk; A. P. Rogachev; N. D. Garbuzenko; N. A. Stamova (Kazimierz Wielki University, 2015)
Gladchuk I. Z., Rogachev A. P., Garbuzenko N. D., Stamova N. A. Utrasonographic monitoring of uterine motility in infertile women with adenomyosis = Ультрасонографический мониторинг маточной перистальтики у бесплодных женщин с аденомиозом. Journal of Education, Health and Sport. 2015;5(12):691-700. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.44823 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%2812%29%3A691-700 https://pbn.nauka.gov.pl/works/695960 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011-2014http://journal.rsw.edu.pl/index.php/JHS/issue/archive           The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport (null) 2391-8306 7 © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 20.12.2015. Revised 25.12.2015. Accepted: 29.12.2015.           UTRASONOGRAPHIC MONITORING OF UTERINE MOTILITY IN INFERTILE WOMEN WITH ADENOMYOSIS Ультрасонографический мониторинг маточной перистальтики у бесплодных женщин с аденомиозом   I. Z. Gladchuk, A. P. Rogachev, N. D. Garbuzenko, N. A. Stamova И. З. Гладчук, А. П. Рогачевский, Н. Д. Гарбузенко, Н. А. Стамова   Odessa National Medical University, Ukraine Одесский национальный медицинский университет, Одесса, Украина   Abstract Taking into account that the uterine pump disruption is one of the leading pathogenic links of infertility in external endometriosis, a significant role of this factor can be detected and in adenomyosis. Diagnosis of uterine peristalsis held with ultrasonography (US), and the study of intrauterine transport was made by hysterosalpingoscintigraphy. Disperistaltic waves at were revealed predominantly in periovulatory phase with the average rate of 4.8 ± 0.23 waves / min. In the control group only single disperistaltic waves throughout the cycle, and their frequency did not exceed 0.4 ± 0.11 waves / min. In all the women with the lack of intrauterine transport  either disperistaltic or complete absence of subendometrial layers of myometrium contractions wave were found.  The significant increase of hysterosalpingoscintigraphy negative results and  contralateral transport depending on the patients' age was revealed (p <0.01 and p <0.05, respectively). Therefore, patients with adenomyosis and impaired uterine peristaltic older than 30 years old should be recommended one of the techniques of extracorporal fertilization with embryo transfer technology, except for intrauterine insemination. Key words: adenomyosis, infertility, uterine pump, uterine peristalsis.   Реферат Учитывая, что нарушение работы маточной помпы - одно из ведущих звеньев патогенеза бесплодия при наружном эндометриозе, может быть обнаружена значимая роль этого фактора и при аденомиозе. Диагностика маточной перистальтики проводится при ультрасонографии (УЗИ), а исследование внутриматочного транспорта - методом  гистеросальпингосцинтиграфии (ГССГ). Дисперистальтические волны при аденомиозе обнаружены преимущественно в периовуляторной фазе со средней частотой 4,8±0,23 волн/мин. В контрольной группе наблюдались только единичные дисперистальтические волны на протяжении всего цикла и их частота не превышала 0,4±0,11 волн/мин. У всех женщин с отсутствием внутриматочного транспорта обнаружены дисперистальтика или полное отсутствие волн сокращения субэндометриальных слоев миометрия. В ходе исследований обнаружено, достоверное увеличение числа случаев отрицательных результатов ГССГ и контралатерального транспорта с возрастом пациенток (р<0,01 и p<0,05, соответственно). Поэтому пациенткам с аденомиозом и нарушением маточной перистальтики старше 30 лет следует рекомендовать одну из методик экстракорпорального оплодотворения с технологией переноса эмбриона, исключая внутриматочную инсеминацию. Ключевые слова: аденомиоз, бесплодие, маточная помпа, маточная перистальтика.